Developing future natural sciences teachers’ readiness to solve pedagogical tasks - Новіцька, Інеса (Pedagogy of Higher and Secondary Education, 2014)
Novytska I. V. Developing future natural sciences teachers’ readiness to solve pedagogical tasks. The article deals with technology elements which deveop future natural sciences teachers’ readiness to solve pedagogical tasks. The author concludes that in the process of forming professional skills in solving the tasks the guiding principles should be followed: to take into account students’ motivation, permanency of teacher education, interdisciplinary approach to studying general, professional and special disciplines, gradual transition from informational education to search and creative one. It was found out that pedagogical situations perform four main functions: diagnostic, teaching, educational and developmental.